2019
DOI: 10.1111/cea.13359
|View full text |Cite
|
Sign up to set email alerts
|

Goblet cell hyperplasia as a feature of neutrophilic asthma

Abstract: Background:Goblet cell hyperplasia (GCH) is a pathological finding classically re-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…Goblet cell differentiation and excessive mucus production are common features of many airway diseases (19) . Patients with COPD and asthma exhibit increased goblet cell hyperplasia and luminal mucin production (20)(21)(22) . MUC5AC levels are increased by goblet cell hyperplasia and metaplasia in sinus mucosa of patients with chronic rhinosinusitis (23,24) .…”
Section: Discussionmentioning
confidence: 99%
“…Goblet cell differentiation and excessive mucus production are common features of many airway diseases (19) . Patients with COPD and asthma exhibit increased goblet cell hyperplasia and luminal mucin production (20)(21)(22) . MUC5AC levels are increased by goblet cell hyperplasia and metaplasia in sinus mucosa of patients with chronic rhinosinusitis (23,24) .…”
Section: Discussionmentioning
confidence: 99%
“…In patients with asthma, tracheal goblet cells undergo hyperplasia and secrete excess mucus that obstructs the airway [ 20 ]. Mucins are glycoproteins produced by airway epithelial cells to clear allergens or microorganisms that invade the respiratory system [ 21 ]. In double IL-4/IL-13 knockout mice, the induction of asthma did not promote tracheal goblet cell hyperplasia and mucin secretion [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Validated questionnaires have been developed to obtain semi-quantitative scales that can be used in clinical trials and daily clinical practice. The Cough and Sputum Assessment Questionnaire (CASA-Q), mostly used in COPD and asthma, is very specific to chronic bronchitis and has the advantage of assessing both symptom intensity and their effects [ 138 , 139 , 140 ]. Strikingly, Alagha et al showed that chronic bronchitis assessed by CASA-Q was not correlated with goblet cell hyperplasia in asthma, calling into question the reliability of such clinical evaluation.…”
Section: Indirect Assessment Of Human Mucus Dysregulationmentioning
confidence: 99%